Functional Neck Dissection: The Operative Technique Series. Issue 5 (November 2016) - Patel, Anup; Clune, James; Ariyan, Stephan
Abstract : Summary: A clinical case of a patient undergoing right functional neck dissection is presented. A detailed, step-by-step video description highlighting the pearls of the operation accompanies the article. This will be the first of many contributions in a Plastic and Reconstructive Surgery and PRS Global Open Operative Technique Series initiative that endeavors to disseminate plastic and reconstructive knowledge worldwide. Abstract : Supplemental Digital Content is available in the text.